COASTAL AND MARINE SUSTAINABLE MANAGEMENT EFFORTS THROUGH CONSERVATION EDUCATION AT EARLY AGE IN THE PARI ISLAND, SERIBU ISLANDS - Sarah Rosemery Megumi Wouthuyzen; Nurdien Harry Kistanto; agus Hartoko; Sam Wouthuyzen (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
The purpose of this study are to introduce coastal resources conservation education and to examine perception of children aged 8-9 years (second grade) of the elementary school, SDN 01 morning Pari Island and also their parents in managing the sustainable of coatal living resources (SDHP) in the future. A qualitative approach in form of action research is used in this study. Data collection was done by observation method, test (pretest and postest) and non test (observation sheet of student and teacher activity, parent interview and key informant) instruments. All data were then analyzed using descriptive method. Results show that the implementation of SDHP conservation education in children aged 8-9 years effectively improve their knowledge and attitude regarding the effort in conserving and managing the SDHP, which expected that the students become agents of change as they grow into adults. On the other hand, the student’s parents strongly support the teaching of conservation and management of SDHP in the early age, since this age is the golden age for them. Unfortunately, in this study there are still many adults community who are reluctant to teach conservation education of SDHP directly to their children, since they are busy in managing their rapidly growing tourism business. In addition, the subject of conservation education of SDHP is still considered not mandatory to be taught. Keywords Conservation education of SDHP, Early age students (8-9 years), Parents, Pari Island